Inflammation and nutritional status in relation to mortality risk from cardio-cerebrovascular events: evidence from NHANES - Hou, Chengzhi; Huang, Xuanchun; Wang, Jie; Chen, Cong; Liu, Chao; Liu, Shuyuan; Li, Hongping (Frontiers in Nutrition, 2024)
ObjectiveInflammation and nutritional status are closely associated with the mortality risk of survivors of cardio-cerebrovascular events. This study aims to evaluate the relationship between inflammation and nutritional indices and mortality among, identifying the most predictive indices.MethodsThis study included cohort data of the survivors of major adverse cardiovascular and cerebrovascular events (MACCE) from the National Health and Nutrition Examination Survey (NHANES) in 1999–2010. MACCE is defined as a composite of myocardial infarction, heart failure and stroke, and at least one of the three events occurs. The main outcomes were all-cause mortality and cardiovascular mortality. Kaplan–Meier analysis and receiver operating characteristic curves were used to compare the correlation between seven inflammatory nutritional indices (such as Advanced Lung Cancer Inflammation Index, ALI) and mortality among the survivors. A multivariable-adjusted Cox regression and restricted cubic splines analysis identified the most predictive index, with the optimal number of nodes determined by the Akaike information criterion. Subgroup and sensitivity analyses were conducted to assess model stability.ResultsA total of 2,045 MACCE survivors were included. The higher levels of ALI and serum albumin were significantly associated with lower risks of all-cause and cardiovascular mortality among these individuals. Increases in C-reactive protein to Lymphocyte Ratio, Neutrophil to Serum Albumin Ratio, Neutrophil-to-Lymphocyte Ratio, Systemic Immune-Inflammation Index (SII), and C-reactive protein were similarly correlated with higher mortality risk. ALI outperformed other indices, displaying a distinct L-shaped nonlinear relationship with both all-cause and cardiovascular mortality among MACCE survivors, with an inflection point at 90 indicating the lowest risk. To the left of this inflection, each unit increase in ALI was associated with a 1.3% decrease in all-cause and cardiovascular mortality risk among MACCE patients. To the right, the risk might increase by 0.2%, although the change was not statistically significant. Subgroup analyses and sensitivity analyses showed that the association between ALI and risk of mortality remained stable in most MACCE survivor populations.ConclusionRoutine and dynamic monitoring of ALI is helpful for clinicians to assess the mortality risk among MACCE survivors. Anti-inflammatory therapies and appropriate nutritional support are crucial for reducing mortality in these individuals.